Charitable giving: The role of framing and information - Keser, Claudia; Kliemt, Hartmut; Späth, Maximilian (PLOS ONE, 2023)
We investigate how different levels of information influence the allocation decisions of donors who are entitled to freely distribute a fixed monetary endowment between themselves and a charitable organization in both giving and taking frames. Participants donate significantly higher amounts, when the decision is described as taking rather than giving. This framing effect becomes smaller if more information about the charity is provided.